O corpo psicanalítico no hospital - Gomes, Daniela Rodrigues Goulart (2008)
Considering that hospitalization implies in the emotional breaking of the ill subject because he/she is faced with vulnerability and abandonment before death and illness, the aim of this work is to make emerge the psychoanalytical body in the hospital through analysis of the psychic of the subject. We performed a reading of the ill-subject in current times, reflecting upon the contemporary knowledge and institutional postures that cross between themselves for the construction and social-cultural representation of the sick and hospitalized body. From the premises of the necessity of controlling the body it is reaffirmed by culture as well as by the institutions, caretakers and assented by the post modern man in search of perfection that mortifies, imposes a mold, that atrophies the feeling of doubt, hesitation, suffering and that even though we observe that this tentative to resist the encounter with doubt by paralyzing subjectivity processes, the actual body, as an announcement, seeks to remember the existence of the pulsional body disclosing the founding insatiability, revealing the suffering that is peculiar to humans, so then as to be born the being is conditions of analysis ,in identity crisis, emerging the subject of speech, the subject of desire. This is the place of the analyst and the analyzed: face to face with the psychoanalytical body. Psychoanalysis has in this work, the role of paraphrasing, a methodological instrument that looks beyond the socialcultural announcement. Psychoanalysis puts itself as an investigator of the logic of the production of meanings- which emerge or are already made up in an institution that treats the urgencies of the body: the public hospital, in the XXI century. The pulsional body is considered here as that one which produces and on which is produces representational fields in which are inserted subjects and is presumed that these fields are governed by specific logic because they are unconscious- and that they determine their relations: be them organic, institutional and subjective, being the subjects are dialectally also made up by them; as the body, at the same time, is the source and aim of the impulses. Two clinical cases studies were analyzed having as an essential operator, the psychoanalytical method which revealed from the transferential relationship of the posture interrogator-interpretant and analytical listening, the ascension of the subject of the unconscious- the subject of desire, psychoanalytic by excellence, reliving interventions that legitimately occupy the trade to which are destined: care for the psychoanalytical body through therapeutic function.